The Impact of Academic Press and Student Teacher Relationship on Childrens Emotional Adjustment - Fadilla Ayuningtyas; Sofia Hartati; Tjipto Sumadi (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2019)
The purpose of this study is to examine the impact of the academic press and student teacher relations on emotional adjustment in children aged 7-8 years. This study used a survey method with 132 respondents in East Jakarta, selected using stratified multistage cluster random sampling. Data collection uses three research instruments in the form of scales 1-3 which is adapted and developed from research indicators using student academic survey press with reliability values (α = .465), short version Student Teacher Relationship Scale (α = .599), and School Liking and Avoidance Questionnaire (α = .715). The results showed that 1) academic press did not had a direct negative effect on emotional adjustment, 2) teacher-student relations had a direct positive effect on emotional adjustment, and 3) academic press and teacher relations simultaneously had a positive effect on emotional adjustment which explained indirect effect of the academic press on emotional adjustment through student teacher relations as a mediator. This indirect influence illustrates that in a state of high positive relations, the academic press's role that the teacher seeks is understood by students as a way for teachers to improve achievement and emotional adjustment. In addition, the positive effect was increasing greater when academic press related together with the teacher-student relationship compared to the partial effect of student relations on emotional adjustment. This greater effect requires a ranking of the partial correlation of the teacher-student relation which is above or greater than the ranking of the partial academic press only.